2019
DOI: 10.5295/cdg.170751dg
|View full text |Cite
|
Sign up to set email alerts
|

New challenges in the improvement of the citizen participation processes of the urban management. Social innovation challenges

Abstract: porque los participantes desconocen las implicaciones económicas, sociales y medioambientales de sus decisiones. La incorporación de nuevas tecnologías a los mecanismos de decisión

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The obtained results not only show which areas can be regarded as accessible in the current situation, but may also be a useful insight for decisions on further transportation network development to make important points of public transport more convenient. In that sense, the study constitutes an approach to support better decision making for sustainable development [42,43], which is an important tool in public transport management [44,45]. Such activity is in line with local policies in many cities aiming to increase the role of public transport in urban mobility [46,47] and as a side effect also increase the value of real estate [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results not only show which areas can be regarded as accessible in the current situation, but may also be a useful insight for decisions on further transportation network development to make important points of public transport more convenient. In that sense, the study constitutes an approach to support better decision making for sustainable development [42,43], which is an important tool in public transport management [44,45]. Such activity is in line with local policies in many cities aiming to increase the role of public transport in urban mobility [46,47] and as a side effect also increase the value of real estate [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of the study showed that much is yet to be accomplished locally in that respect. Other recent works in the Spanish context analyse mechanisms for improving participation at the local level [90,91].…”
Section: Methodsmentioning
confidence: 99%
“…Hence an effort is still necessary in this regard, as it represents a crucial part of a decarbonisation plan. In this sense, a tool able to show the participants the potential affections of the different scenarios would reinforce the quality of the envisioning engagement process [23]. Furthermore, as requested by some pioneer cities in climate neutrality terms (i.e., Copenhagen), the modelling, visioning, and planning processes must offer the opportunity of accounting not just the impact of energy consumption within the city but also all other GHG emissions that occur outside the city boundary as a result of activities taking place within the city boundary (i.e., supply chains of non-energy good, such as food, water, building materials, clothing, products, etc.)…”
Section: Key Local Stakeholders At the Corementioning
confidence: 99%